MENINGKATKAN KEMAMPUAN MENULIS PUISI BALI MODERN DENGAN MENERAPKAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) PADA SISWA KELAS VII H SMP DHARMA WIWEKA DENPASAR TAHUN PELAJARAN 2021/2022” - Arya Suci Ratna Dewi (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2022)
The ability to write modern Balinese poetry in class VII H SMP Dharma Wiweka Denpasar  is still low. To overcome this, the researcher offers to apply the Team Assisted Individualization type of cooperative learning model. The formulation of the problem in this study are: (1) Can the application of the Team Assisted Individualization (TAI) learning model improve the ability to write modern Balinese poetry for students of class VII H SMP Dharma Wiweka Denpasar ? (2) How are the students of class VII H SMP Dharma Wiweka Denpasar responding to the application of the Team Assisted Individualization (TAI) learning model? The application of the Team Assisted Individualization (TAI) learning model can improve the ability to write modern Balinese poetry in class VII H SMP Dharma Wiweka Denpasar . This can be seen from the test results of students in the first cycle obtaining an average score of 76.19 with a total percentage of 71.79%. In the second cycle there was an increase with an average score of 83.14 with a total percentage of 89.74%, besides that an increase also occurred in student responses with an average score of 12.43 in the first cycle to 16.76 in the second cycle from a maximum score of 20 with a very positive category. It is recommended that Balinese language teachers apply the Team Assisted Individualization (TAI) learning model in learning to write modern Balinese poetry, students are advised to improve their abilities by practicing more in writing modern Balinese poetry, for the school the Team Assisted Individualization (TAI) learning model can be used as a learning model. material for consideration to be applied to other lessons. Keywords: Team Assisted Individualization (TAI) model, writing modern Balinese poetry.